PERAN ORANG TUA DAN KEPALA SEKOLAH DALAM PEMBINAAN AKHLAK SISWA DI MTS ZAHROTUL ISLAM TEGALREJO DRINGU PROBOLINGGO - Holilah, Nur; Muhammad, Devy Habibi; Adawiyah, Robiatul (IMTIYAZ: Jurnal Ilmu Keislaman, 2024)
This research explores the role of parents and school principals in developing student morals at MTS Zahrotul Islam Tegalrejo Dringu Probolinggo. Using a descriptive qualitative approach, data was collected through interviews, observation and documentation at a school. Qualitative analysis was carried out to process field data with the steps of Data Collection, Data Reduction, Data Presentation, and Drawing Conclusions. The focus of the research is the validity of data regarding "The Role of Parents and Principals in Developing Student Morals at MTS Zahrotul Islam Tegalrejo Dringu Probolinggo." Research findings show that close collaboration between parents and school principals has a positive impact in shaping students' character and morals, as well as creating a learning environment that is oriented towards ethical values. Several key factors that support successful collaboration include open communication between parents and the school, the role of the principal as a moral leader, and active participation of parents in school activities. This research provides insight into strategies that can be implemented to improve student moral development. It is hoped that the implications of this research can contribute to parents, teachers and schools by understanding the roles played by parents and school principals. It is hoped that schools can develop more holistic programs to shape student character. In addition, this research highlights challenges in implementing moral development, such as differences in cultural values between home and school. The success of developing student morals is very dependent on cooperation and mutual commitment between parents and the school. Keywords:  Role; Moral Development